Appunti su storia, verità e diritto. A proposito della Risoluzione del Parlamento europeo sull’importanza della memoria europea - Magnani, Carlo (Cultura giuridica e diritto vivente, 2020)
[Notes on history, truth and law. On the European Parliament resolution on the importance of European memory] The text constitutes a first reading of the European Parliament resolution (2019/2819(RSP)). The Italian constitutional model of freedom of speech is liberal and open-minded, not suited to official visions of truth and historical memory. Finally, the text of the Resolution will be critically analysed in the light of the constitutional model. This Resolution is rather weak in its historiographical part and presents very marked ideological profiles.